2008
DOI: 10.11646/zootaxa.1957.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A revision of Oriental Teloganodidae (Insecta, Ephemeroptera, Ephemerelloidea)

Abstract: Based on the examination of the type series of Cloe tristis Hagen, 1858 (type species of the genus Teloganodes Eaton, 1882) and material housed in several institutions, a revision of Oriental Teloganodidae is proposed. A lectotype is designated for Teloganodes tristis (Hagen, 1858) and the genus is redefined. The species T. major Eaton, 1884, is a subjective junior synonym of T. tristis Hagen, 1858 (syn. nov.). The genus Macafertiella Wang, 1996 is a subjective junior synonym of Teloganodes Eaton, 1882 (syn. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…As reported in Sartori et al 2008, the antenna length relative to the head width also varies between species. While most Philippine species reported here have an antenna length subequal to the head width, in Dudgeodes luntian sp.…”
Section: Headmentioning
confidence: 60%
See 1 more Smart Citation
“…As reported in Sartori et al 2008, the antenna length relative to the head width also varies between species. While most Philippine species reported here have an antenna length subequal to the head width, in Dudgeodes luntian sp.…”
Section: Headmentioning
confidence: 60%
“…Paratypes of other Southeast Asian species of Dudgeodes deposited in the Museum of Zoology, Lausanne, Switzerland (MZL) were examined for morphological comparisons and supplementary descriptions. Terminologies followed Sartori et al (2008) and Martynov et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…It has already been demonstrated that the subimaginal stage may retain some nymphal structures, such as gill sockets (Sartori et al 2008), which may help to link nymphal and winged stages. The presence of vestigial tubercles on the terga thus indicates that the nymph possesses a median single ridge on the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Ulmer’s collection, the ZMH also stores primary type material described by other authors, such as Klapalek (1905a,b), Lestage (1930, 1935), Malzacher (1976, 2015, 2016), Müller-Liebenau (1971, 1974, 1980a, b, 1981), and Sartori (2008, 2014e). An interesting finding was the discovery of several paratypes of species described by Esben-Petersen (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Peters and Edmunds 1972; Puthz 1977; Braasch and Soldán 1986; Campbell and Suter 1988; Gillies 1990; Grant and Peters 1993; McCafferty and Waltz 1995; Lugo-Ortiz and McCafferty 1996, 1999; Sartori et al 2008; Sartori 2014a, b, c. ).…”
Section: Introductionmentioning
confidence: 99%